Retroarc volcanism in the northern San Rafael Block (34°-35°30′S), southern Central Andes: Occurrence, age, and tectonic setting - Folguera Telichevsky, Andres (2009)
One of the major retroarc volcanic provinces in the southern Central Andes (34° and 37°S) is developed in the Andean foothills of the San Rafael region between the orogenic front and foreland basement uplifts of Late Miocene age. Here we present the first comprehensive geochronological study of the Quaternary volcanism, previously dated mainly on the basis of stratigraphy. The new unspiked K-Ar radiometric and two radiocarbon determinations encompass many volcanic centers, most of them monogenetic and of basaltic composition exposed between 34° and 35°30′S. The data constrains the basaltic volcanism to between ~ 1.8 Ma and the Holocene. The spatiotemporal distribution of the ages indicates that eruption in the retroarc was episodic with some distinct patterns. The orogenic front of the San Rafael Block is associated with 1.8-0.7 Ma volcanic eruptions, while the Malargüe fold and thrust belt front in the Andean foothills is related to younger eruptions produced at 0.1-0.01 Ma. Both areas are associated with Late Cenozoic normal faults that dismembered an uplifted a Late Miocene peneplain as indicated by younger over older fault-relationships between Paleozoic rocks and Tertiary strata. This linkage indicates a major relationship between Pleistocene-Holocene retroarc eruptions of the basaltic centers, and extensional collapse of the foreland region, that shows a migration of the last volcanic activity towards the trench.